19.02: Exploring the potentials of metal foams in structural elements for civil/building applications. (13th September 2017) - Faiella, Diana; Viscovo, Simona; Mele, Elena
ABSTRACT: Sandwich foam beams and panels, made of solid skins and aluminium foam core, are widely applied in high‐tech engineering fields; on the contrary structural use in the civil engineering field is not so common. An initial, explorative study on the structural application of metal foams in the civil and building engineering field is presented in this paper. The potentials of sandwich foam beams, made of solid skins (aluminium or steel) and aluminium foam core, are studied through analytical models and parametric analyses. The sandwich flexural response is investigated under four point bending test. For this purpose, an analytical tool able to provide design indications for sandwich foam beams is presented and applied in a parametric analysis, adopting some commercial aluminium foams and skins both in steel and aluminium alloys. The cross section failure modes under bending action (namely: skin fracture, core fracture, face wrinkling, ) are studied, and failure mode maps are proposed for different combinations of solid‐skins–foam‐core in order to identify the dominant failure mode varying the skin thickness to beam depth ratio for practical design purposes. An experimental campaign is being planned to validate the presented results.